ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 19/PUU- XII/2014 TERHADAP TAFSIRAN FRASA “KOMITE OLAHRAGA” - Aisyah Hatta Lianda; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
KONI filed a lawsuit through the Constitutional Court to conduct a judicial review ofthe SKN Law with constitutional case register Number 19/PUU-XII/2014, one of the objectsof testing is Article 36 paragraphs (1) and (3) of the SKN Law related to the phrase "sportscommittee" where KONI believes that the emergence of these phrases makes KONI not havestrong legitimacy to carry out its authority as a partner institution of the Government insports management so far. Therefore, the purpose of this thesis research is first, to analyzethe considerations of the Constitutional Court judges in Decision Number 19/PUU-XII/2014on the interpretation of the phrase "sports committee" in Article 36 paragraphs (1) and (3) ofthe SKN Law. Second, knowing the legal implications of the interpretation of the phrase"sports committee" in Decision Number 19/PUU-XII/2014 on the position of the nationalsports committee.This type of research can be classified into the type of normative legal research. Thisstudy used secondary data consisting of primary legal materials, secondary legal materials,tertiary legal materials and data collection techniques were carried out using the librarystudy method.From the results of the research problem there are two main things that can beconcluded. First, in the legal considerations and judges' decisions in Decision Number19/PUU-XII/2014, the Constitutional Court used several approaches to constitutionalinterpretation that had fulfilled the principles of constitutional interpretation and gave averdict, namely the Constitutional Court interpreted that the phrase "sports committee" inArticle 36 paragraphs (1) and (3) of the SKN Law did not cause multiple interpretationsbecause the formation of the SKN Law was not intended to only form one national sportsorganization. Although so, the Constitutional Court is firm in accommodating pluralinstitutions in related decisions, it can also be seen that in its legal considerations, ifinterpreted more deeply, the Constitutional Court also leads to the concept of open legalpolicy. Second, the legal implication after the enactment of Decision Number 19/PUU-XII/2014 related to the interpretation of the phrase "sports committee" is the problem ofposition in the sports development of the two main national sports institutions in Indonesia,namely KONI and KOI. The author's suggestions: First, the Constitutional Court needs todevelop an approach related to the use of constitutional interpretation and provideconfirmation of when a policy falls into the constitutional / unconstitutional category andwhen a policy falls into the concept of open legal policy. Thus, it is clear about how toproperly implement the Constitutional Court's decision. Second, there needs to be aGovernment Regulation that regulates each national sports committee as a follow-up to theConstitutional Court Decision and as a form of coordination between existing institutions bypaying attention to proportionality goals that do not harm security and public interests,especially the issue of competing rights in the future.Keywords: Sports Commitee, Constitutional Interpretation, open legal policy.